Opportunities for Small Molecules in Cancer Immunotherapy. Issue 6 (June 2020) - van der Zanden, Sabina Y.; Luimstra, Jolien J.; Neefjes, Jacques; Borst, Jannie; Ovaa, Huib
Abstract : Cancer immunotherapy has proven remarkably successful through instigation of systemic antitumor T cell responses. Despite this achievement, further advancements are needed to expand the scope of susceptible cancer types and overcome variation in treatment outcomes between patients. Small-molecule drugs targeting defined pathways and/or cells capable of immune modulation are expected to substantially improve efficacy of cancer immunotherapy. Small-molecule drugs possess unique properties compatible with systemic administration and amenable to both extracellular and intracellular targets. These compounds can modify molecular pathways to overcome immune tolerance and suppression towards effective antitumor responses. Here, we provide an overview of how such effects might be achieved by combining immunotherapy with conventional and/or new small-molecule chemotherapeutics. Highlights: Conventional and novel targeted chemotherapeutics often have immunomodulatory effects (still largely undefined); thus, we posit that new small-molecule drugs can be designed and selected to promote T cell responses against certain cancers. Small molecules have cell-penetrating capabilities, rendering them suitable for targeting intracellular proteins. In addition, their general shorter half-lives potentially reduce the risk of systemic toxicity due to limited accumulation in the circulation. Combining novel small-molecule drugs with antibody-based checkpoint blockade may offer targeted, mechanism-guided, rational advances in cancer immunotherapy. Small-molecule drugs may provide valuable opportunities to increase efficacy of all cancer immunotherapy strategies by increasing tumor immunogenicity and overcoming tumor-associated immunosuppression.